2015
DOI: 10.19076/mta.19726
|View full text |Cite
|
Sign up to set email alerts
|

Gökçeada’nin (Çanakkale) Jeoloji̇si̇

Abstract: The geology and especially the magmatic rocks of Gökçeada, which is the biggest island of Turkey and located at 20 km's west of Biga Peninsula, constitute the subject of this study. Late Ediacaran/Early Paleozoic aged Çamlıca metamorphics which crop out with a tectonic uplift in a narrow area in northwest of Gökçeada are the oldest rocks of the island. Early Eocene aged Karaağaç Formation which is formed by submarine fan deposits unconformably overlies Çamlıca metamorphics. As for the Dağiçitepe volcanic membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Considering all taxonomic studies on freshwater macroinvertebrates on the Aegean Islands, Gökçeada Island was found to occupy a prominent place among them in terms of macroinvertebrate diversity. It was hypothesized that habitat diversity (ponds, reservoirs, streams, and springs), geographical location and relief (Sarı et al 2015) were the main driving factors that increase the aquatic biodiversity of Gökçeada.…”
Section: Figurementioning
confidence: 99%
“…Considering all taxonomic studies on freshwater macroinvertebrates on the Aegean Islands, Gökçeada Island was found to occupy a prominent place among them in terms of macroinvertebrate diversity. It was hypothesized that habitat diversity (ponds, reservoirs, streams, and springs), geographical location and relief (Sarı et al 2015) were the main driving factors that increase the aquatic biodiversity of Gökçeada.…”
Section: Figurementioning
confidence: 99%